Matrix metalloproteinase-9 plays a role in protecting zebrafish from lethal infection with Listeria monocytogenes by enhancing macrophage migration. (July 2016) - Shan, Ying; Zhang, Yikai; Zhuo, Xunhui; Li, Xiaoliang; Peng, Jinrong; Fang, Weihuan
Abstract: Zebrafish could serve as an alternative animal model for pathogenic bacteria in multiple infectious routes. Our previous study showed that immersion infection in zebrafish with Listeria monocytogenes did not cause lethality but induced transient expression of several immune response genes. We used an Affymetrix gene chip to examine the expression profiles of genes of zebrafish immersion-infected with L . monocytogenes . A total of 239 genes were up-regulated and 56 genes down-regulated compared with uninfected fish. Highest expression (>20-fold) was seen with the mmp-9 gene encoding the matrix metalloproteinase-9 (Mmp-9) known to degrade the extracellular matrix proteins. By morpholino knockdown of mmp-9, we found that the morphants showed rapid death with much higher bacterial load after intravenous or intraventricular (brain ventricle) infection with L . monocytogenes . Macrophages in mmp-9 -knockdown morphants had significant defect in migrating to the brain cavity upon intraventricular infection. Decreased migration of murine macrophages with knockdown of mmp-9 and cd44 was also seen in transwell inserts with 8-μm pore polycarbonate membrane, as compared with the scrambled RNA. These findings suggest that Mmp-9 is a protective molecule against infection by L . monocytogenes by engaging in migration of zebrafish macrophages to the site of infection via a non-proteolytic role. Further work is required on the molecular mechanisms governing Mmp-9-driven macrophage migration in zebrafish. Highlights: Transcriptomic analysis of germ-free zebrafish immersion-infected with Listeria. Mmp-9 was the most up-regulated gene following immersion infection with Listeria. Mmp-9 is a host defense factor to infection by mobilizing macrophage migration. Mmp-9 is involved in macrophage migration via a non-proteolytic activity.